Consumption of an Anthocyanin-Rich Extract Made From New Zealand Blackcurrants Prior to Exercise May Assist Recovery From Oxidative Stress and Maintains Circulating Neutrophil Function: A Pilot Study - Hurst, Roger D.; Lyall, Kirsty A.; Roberts, Joanna M.; Perthaner, Anton; Wells, Robyn W.; Cooney, Janine M.; Jensen, Dwayne J.; Burr, Natalie S.; Hurst, Suzanne M. (Frontiers in Nutrition, 2019)
Aim: To evaluate blackcurrant anthocyanin-rich extract (BAE) consumption on time- and dose-dependent plasma anthocyanin bioavailability and conduct a pilot study to explore the potential effect of BAE in promoting recovery from exercise-induced oxidative stress, and maintenance of circulating neutrophil function. Methods: Time- and dose-dependent blackcurrant anthocyanin bioavailability was assessed using LC-MS in 12 participants over 6 hr after the ingestion of a placebo or BAE containing 0.8, 1.6 or 3.2 mg/kg total anthocyanins. In a separate pilot intervention exercise trial, 32 participants consumed either a placebo or 0.8, 1.6 or 3.2 mg/kg BAE (8 individuals per group), and then 1 hr later performed a 30 min row at 70% VO2max. Blood was collected during the trial for oxidative, antioxidant, inflammatory and circulating neutrophil status. Results: Consumption of BAE caused a time- and dose-dependent increase in plasma anthocyanins, peaking at 2 hr after ingestion of 3.2 mg/kg BAE (217 ± 69 nM). BAE consumed 1 hr prior to a 30 min row had no effect on plasma antioxidant status but hastened the recovery from exercise-induced oxidative stress: By 2 hr recovery, consumption of 1.6 mg/kg BAE prior to exercise caused a significant (P<0.05) 34% and 32% decrease in post-exercise plasma oxidative capacity and protein carbonyl levels respectively, compared to placebo. BAE consumption prior to exercise dose-dependently attenuated a small, yet significant (P<0.01) transient 13 ± 2% decline in circulating neutrophils observed in the placebo group immediately post-exercise. Furthermore, the timed consumption of either 1.6 or 3.2 mg/kg BAE attenuated a 17 ± 2.4% (P<0.05) decline in neutrophil phagocytic capability of opsonised FITC-Escherichia coli observed 6 hr post-exercise in the placebo group. Similarly, a dose-dependent increase in neutrophil surface expression of complement receptor-3 complex (CR3, critical for effective phagocytosis of opsonised microbes), was observed 6 hr post-exercise in both 1.6 and 3.2 mg/kg BAE intervention groups. Conclusions: Consumption of BAE (>1.6 mg/kg) 1 hr prior to exercise facilitated recovery from exercise-induced oxidative stress and preserved circulating neutrophil function. This study provides data to underpin a larger study designed to evaluate the efficacy of timed BAE consumption on post-exercise recovery and innate immunity.